2007
DOI: 10.1007/s11418-007-0143-x
|View full text |Cite
|
Sign up to set email alerts
|

The chemical constituents of fresh Gentian Root

Abstract: We isolated and characterized 23 compounds, including a new iridoid named gentiolutelin and its dimethyl acetal, and a new lignan named gentioluteol from fresh roots (including small amounts of rhizome) of Gentiana lutea cultivated in Japan (Hokkaido). The structures of gentiolutelin and gentioluteol were determined as (1S,2R,3S,5R)-3-hydroxy-2-methyl-5-(2-oxoethyl)-cyclopentanecarboxylic acid methyl ester and (7R,8S,8¢S)-4,4¢,8,9-tetrahydroxy-3,3¢,5-trimethoxy-7,9¢-epoxylignan, respectively, on the basis of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 36 publications
1
36
0
1
Order By: Relevance
“…Ando et al (2007) indicated that the gentiopicroside content is strongly affected by the stage and environment of development of the plant and the preparation process. The biosynthesis of secoiridoids in Gentianaceae plants can be related to the physiological development stage which is affected by plant age, physiology and growing environment of the plant (Piatczak et al 2006;Zhang et al 2010).…”
Section: Pcr Analysis Of Transgenic Hairy Rootsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ando et al (2007) indicated that the gentiopicroside content is strongly affected by the stage and environment of development of the plant and the preparation process. The biosynthesis of secoiridoids in Gentianaceae plants can be related to the physiological development stage which is affected by plant age, physiology and growing environment of the plant (Piatczak et al 2006;Zhang et al 2010).…”
Section: Pcr Analysis Of Transgenic Hairy Rootsmentioning
confidence: 99%
“…The quality of the root is evaluated by the major bitter principle gentiopicroside. Increasing demand for raw material (1,500 tons of gentian roots) has caused significant damage in their natural habitats (Ando et al 2007). For those reasons, nearly 100 species of this genus are protected by law in many European countries (Mikula et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EtOAc, n-BuOH, and water extracts, which contained aromatic compounds as assessed by HPLC, were separately chromatographed using YMC gel ODS-AQ, Sephadex LH-20, and/or Chromatorex ODS with methanol (MeOH) [or ethanol (EtOH)]-H 2 O in stepwise gradient mode. The fractions showing similar HPLC patterns were combined and further purified by column chromatography, to afford loganic acid 7-(2′-hydroxy-3′-O-β-D-glucopyranosyl)benzoate (1), together with 5-hydroxymethyl-2-furfural (2), 12) furan-2-carboxylic acid (3), 13) 2,3-dihydroxybenzoic acid (4), 14) gentiopicroside (5), 5) isovitexin (6), 15) gentisin 7-O-primeveroside (7), 7) isogentisin 3-O-primeveroside (8), 16) a mixture of gentisin (9) and isogentisin (10), 4) vanillic acid (11), 17) loganic acid (12), 4) sweroside (13), 15) 6′-O-glucosylgentiopicroside (14), 16) and swartiajaposide D (15). 18) The n-hexane extract was dissolved in acetone and subjected to preparative TLC to give anofinic acid (16) and 2-methoxyanofinic acid (17), 4) The known compounds were identified by direct comparison with authentic specimens or by spectral comparison with data reported in the literature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3) Previously, phytochemical studies of this drug revealed the presence of bitter secoiridoid glycosides, including gentiopicroside, swertiamarin, and amarogentin, [4][5][6] xanthones, 7) phenolic acids, 8) flavonoids, 9) and triterpenoids. 10,11) Notably, water or ethanolic extract of the gentian root and rhizome is used to impart a bitter taste to liqueurs.…”
mentioning
confidence: 99%